1979
DOI: 10.1073/pnas.76.7.3411
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ribosomal protein synthesis in Escherichia coli by selective mRNA inactivation.

Abstract: In an Escherichia coli strain lysogenic for Xspc2 transducing phage, an extra copy of ribosomal protein (r-protein) genes in the spc and a operons are carried on the phage chromosome. Expression of genes in the spc operon in this merodiploid strain was compared with that in a control "haploid" strain carrying XtrkA phage. It was found that the synthesis rate of spc mRNA, relative to other reference mRNA in the merodiploid strain, is about 2-fold higher than that in the control strain; yet, no dosage effect was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…It is of interest to note that the lack of gene dosage effect has been reported for the synthesis of ribosomal proteins [ 18-241 and of the /3 and 0' subunits of RNA polymerase [ 171. In some cases [20,21,231, it has been shown that the rate of transcription of mRNA increases as the number of the corresponding gene copies increases, yet no dosage effect was observed in the synthesis of the respective proteins. This suggests that expression of these genes may be regulated by post-transcriptional control, including the inactivation or degradation of mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to note that the lack of gene dosage effect has been reported for the synthesis of ribosomal proteins [ 18-241 and of the /3 and 0' subunits of RNA polymerase [ 171. In some cases [20,21,231, it has been shown that the rate of transcription of mRNA increases as the number of the corresponding gene copies increases, yet no dosage effect was observed in the synthesis of the respective proteins. This suggests that expression of these genes may be regulated by post-transcriptional control, including the inactivation or degradation of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that expression of these genes may be regulated by post-transcriptional control, including the inactivation or degradation of mRNA. This regulation was interpreted by a model in which free ribosomal proteins, when overproduced, selectively inactivate their own mRNA by a feedback mechanism [ 19,20,24]. It remains to be seen whether the similar regulatory mechanism may be present in the case of EF-Tu biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1970s, it was proposed that autoregulatory ribosomal proteins bind their own mRNAs the same way they bind to rRNA in the ribosome because their mRNAs and rRNAs have locally similar three-dimensional structure (Fallon et al 1979;Lindahl and Zengel 1979;Fiil et al 1980;Nomura et al 1980). This idea was attractive because if the RNA-binding activity that enables these proteins to participate in ribosome assembly also causes translational regulation, competition between rRNAs and ribosomal protein mRNAs will guarantee that the production of ribosomal proteins decreases when supply exceeds demand.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal protein (r-protein} gene expression is coordinated with cellular metabolism in bacteria through autoregulatory mechanisms that operate at the levels of transcription Skouv et al 1990;, mRNA processing (Fallon et al 1979;Mackie 1991), and protein biosynthesis Cole and Nomura 1986;Kearney and Nomura 1987;Thomas et al 1987;Mattheakis et al 1989;Portier et al 1990;Wikstr6m et al 1992). Yeast strains employ a similar set of control mechanisms to regulate r-protein gene expression during (Della Sita et al 1990;Mager andPlanta 1990, 1991;Moehle and Hinnebusch 1991;Presutti et al 1991;Papciak and Pearson 1992) and after (Gorenstein and Warner 1976;Kief and Warner 1981;Pearson et al 1982;Warner et al 1985;Dabeva and Warner 1993) transcription.…”
mentioning
confidence: 99%